PERANCANGAN SISTEM PENGELOLAAN DATA PENERIMA DANA ZAKAT, INFAQ DAN SEDEKAH MENGGUNAKAN FRAMEWORK LARAVEL - Syahidan Mushab Al Zikri (Universitas Teknokrat Indonesia, 2021)
This research was conducted on the basis of the need for a data management system of zakat, infaq and alms recipients that can be used to manage the utilization data (PDG) on IZI Lampung. In the construction of this system using the waterfall model method, as well as system analysts who run using PIECES analysis. Data collection by way of interviews and observations on IZI Lampung. PIECES analysis is used to make comparisons between the old system and the new system to be created as well as determine the analysis of functional needs, and non-functional needs. This data management system is designed with UML (Unified Modeling Language) system development tools consisting of use case diagrams, activity diagrams, sequence diagrams and class diagrams. In creating this system using mySQL database and text editor sublime text 3 by using laravel framework and PHP programming language. In this system there is a data input system, data search, data editing, data updates and report collection that makes it easier for users to find data, change data and update the desired data